2016
DOI: 10.1016/j.jvs.2016.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of the Use of Glyceryl Trinitrate Patches to Aid Arteriovenous Fistula Maturation

Abstract: Conclusions:In the UK National Health Service (NHS) abdominal aortic aneurysm (AAA) screening programs are effective in detecting AAA and lead to effectively treating men with AAA.Summary: Approximately 3000 to 4000 people die from ruptured AAA each year in England and Wales. Most of the deaths occur in men over 65 years of age. Population screening of men $65 years of age for AAA in the UK began in 2009 and was implemented in all of England by April 2013. The current study presented here reviews the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…There is little favorable evidence of locally applied glyceryl trinitrate transdermal patch with supporting evidence from small observational studies. 31 However, our findings demonstrate no benefit of glyceryl trinitrate in supporting AVF maturation.…”
Section: Discussioncontrasting
confidence: 59%
“…There is little favorable evidence of locally applied glyceryl trinitrate transdermal patch with supporting evidence from small observational studies. 31 However, our findings demonstrate no benefit of glyceryl trinitrate in supporting AVF maturation.…”
Section: Discussioncontrasting
confidence: 59%
“…In addition to these reviews, we identified six RCTs published after 2013 and not included in any of the considered systematic reviews, assessing various adjuvant medical treatments for improving AV access patency [24][25][26][27][28][29].…”
Section: Rationale • Backgroundmentioning
confidence: 99%
“…Glyceryl trinitrate was tested in a placebo-controlled clinical trial including 200 participants [27]. An active or a placebo patch was applied 5 cm proximal to the AV anastomosis immediately after completing the surgical procedure and left in place for 24 h. The trial provided moderate-certainty evidence for no meaningful difference in patency at 6 weeks or change in venous diameter as a surrogate for maturation.…”
Section: Glyceryl Trinitratementioning
confidence: 99%